‘ETHICS OF MERCY’ AND THE VISION OF ‘ZIELGEBOT’: EMERGING MORAL TRENDS IN CONTEXT - Darsi, Don Bosco (Asian Horizons, 2015)
In this article, we aim to sketch the main lines of ethics which we dare to call an ‘Ethics of Compassion’. This model makes a moral analysis of the quality of the ‘end, intention, choice of behaviour and the given circumstances’. It implies first of all, an ‘ethics of attainable’ rooted in God’s gracious compassion. Beyond the subjective dimension of meaning and objective dimension of meaning, we require a ‘visionary ethics’ in the perspective of qualitative-desirable. Although Catholic Church sets high moral standards, we believe God is not a cosmic police officer. A meaningful and integrated life moves towards a ‘goalcommandment’ (‘Zielgebot’). Even if all don’t make it to the top (vere bonum — full good), everyone is capable of at least reaching a certain level (minus bonum — lesser good). Therefore, no one should be abandoned at the foot of the mountain. A little push and motivational encouragement would always be a big help. Even those people with limited possibilities are important in the framework of a realistic ethics of attainable. A shift from the classic top-down paradigm to ‘from below’ paradigm of compassion and tolerance is the new trend. It helps one to turn away from the present deviant behaviour towards the desirable behaviour. To withdraw into ‘canon law liberty’ does not easily help people in all the contemporary messiness of their lives. With the idea of Zielgebot, ethics of gradualness makes people more compassionate. The application of the ethics of compassion to marriage was one of the important issues at the recent synod on the family.